CHARACTERISATION AND ACOUSTIC CORRECTION OF CLASSROOMS, CASE STUDY: FACULTY OF ARCHITECTURE IN CONSTANTINE, ALGERIA - Zohra Benmaghsoula (International Journal of Innovative Technologies in Social Science, 2024)
Teaching spaces such as classrooms are spaces intended to communicate pedagogical content orally to learners, and for this function their design must ensure listening comfort through appropriate choice of finishing materials and correct acoustic design. In room acoustics, the acoustic characterization of spaces is done by calculating certain acoustic criteria, in order to conclude whether the acoustics are good or bad. The simulation evaluation of a space makes it possible to calculate objective criteria such as reverberation time, speech intelligibility and clarity in addition to background noise and to carry out an acoustic correction. The objective of this work is to evaluate, using the tool of simulation, the variation of the acoustic conditions of two classrooms similar in their architecture but which differ by the height of the ceiling and therefore have different volumes. In order to obtain optimal values for the two classrooms of the calculated acoustic criteria, the absorbent materials will be placed according to the architectural peculiarities of the two workshops.